2015
DOI: 10.1111/bph.13191
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological actions of nobiletin in the modulation of platelet function

Abstract: Background and PurposeThe discovery that flavonoids are capable of inhibiting platelet function has led to their investigation as potential antithrombotic agents. However, despite the range of studies on the antiplatelet properties of flavonoids, little is known about the mechanisms by which flavonoids inhibit platelet function. In this study, we aimed to explore the pharmacological effects of a polymethoxy flavonoid, nobiletin, in the modulation of platelet function.Experimental ApproachThe ability of nobilet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…Moreover, at a maximum concentration of 30 µ M, nobiletin had no effects on the intracellular levels of cyclic AMP or cyclic GMP in human platelets, which is consistent with the recent observation by Vaiyapuri et al (21). Of note, our preliminary experiments revealed that nobiletin (30 µ M) markedly increased VASP phosphorylation in a similar manner to prostaglandin E 1 (PGE 1 ) (Fig.…”
Section: Introductionsupporting
confidence: 92%
“…Moreover, at a maximum concentration of 30 µ M, nobiletin had no effects on the intracellular levels of cyclic AMP or cyclic GMP in human platelets, which is consistent with the recent observation by Vaiyapuri et al (21). Of note, our preliminary experiments revealed that nobiletin (30 µ M) markedly increased VASP phosphorylation in a similar manner to prostaglandin E 1 (PGE 1 ) (Fig.…”
Section: Introductionsupporting
confidence: 92%
“…Moreover, quercetin (25–100 μM) inhibited collagen‐induced fibrinogen binding to its receptor, perhaps by causing conformational changes to the GPIIb IIIa receptor, thus reducing the affinity of fibrinogen for the receptor binding site (Oh et al , ). Similar findings have been reported for nobiletin (6.25–200 μM), a flavonoid found in citrus fruit (Vaiyapuri et al , ).…”
Section: Polyphenols As Pharmacological Agentssupporting
confidence: 89%
“…Numerous studies have investigated the possible BP-lowering effect of different flavonoids, such as Apocynum venetum and rutin [30,33,34,35]. Nobiletin has been shown to lower cholesterol and improve microcirculation properties [36]. However, the antihypertensive effect of nobiletin has not been investigated.…”
Section: Discussionmentioning
confidence: 99%